The Effect Of Employee Training And Development On Mediated Employee Retention By Job Satisfaction In The Secretariat Mandailing Natal Regency DPRD - Afrizal; Mesra B (Yayasan Multidimensi Kreatif, 2025)
Proper employee training and development as well as high job satisfaction are important factors in retaining employees in government organizations. This study aims to find out and analyze the effect of training and development on employee retention mediated by job satisfaction at the Secretariat of the Mandailing Natal Regency DPRD. This study uses a causal associative quantitative approach. The sample used was the entire employee population totaling 145 people, with a saturated sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that training and development had a positive and significant effect on employee retention, with a T-statistical value of 2.189 > 1.96 and a P-value of 0.031 < 0.05, indicating that training and development can increase employee retention. In addition, training and development had a positive and significant effect on job satisfaction, with a T-statistical value of 40.287 > 1.96 and a P-value of 0.000 < 0.05, which indicates that training and development are able to increase employee job satisfaction. Job satisfaction also had a positive and significant effect on employee retention, with a T-statistical value of 3.930 > 1.96 and a P-value of 0.000 < 0.05, which showed that increasing job satisfaction could increase employee retention. In addition, job satisfaction was able to mediate the influence between training and development on employee retention, shown by a T-statistical value of 3.884 > 1.96 and a P-value of 0.000 < 0.05. These results provide insight that training, development, and job satisfaction are effective strategies in increasing employee retention at the Mandailing Natal Regency DPRD Secretariat